Spinal Anesthesia for a Rh Isommunized Pregnancy with Autologous Blood Transfusion: A Case Report - Pragya Preet Kaur; Yudhyavir Singh; Amit Kumar; Nivedha Giridharan (Wolters Kluwer Medknow Publications, 2023)
Autologous blood transfusion is defined as the collection of blood from the patient, either preoperatively or intraoperatively, and its transfusion back to the same patient as and when required. We report a case of a 23-year-old pregnant female, G3P1L1A1, presenting with severe Rh alloimmunization, along with a baby requiring intrauterine transfusion for fetal anemia, planned for elective cesarean section and autologous blood transfusion.